Black book vol. 3: research report and presentation guidelines for ADS555 / Mahadir Ladisma @ Awis … [et al.] - Ladisma @ Awis, Mahadir; Rabun, Mohd Nazir; Mohamed Harith, Nor Hafizah; Arshad, Mohd Ramlan; Ahmad, Yarina (Division of Research and Industry Linkages, 2017)
In the process of completing their Bachelor degree, all final semester students are required to submit their research reports in fulfillment of the requirements for the Degree of Bachelor o f Administrative Science. Although, it is understood that the students may face various challenges and issues in completing their research project, students are reminded that consistency and accuracy of the submitted research reports are important. A form of guidance to help the students is necessary to ensure a progressive research project and to avoid delay the completion o f their research reports could be put into action. Students are emphasized the need to carry out their research report in an organized and a systematic way. In lights of the above context, the improved volume of Black Book (in short, BB) Vol.3 is introduced to accommodate the research process by highlighting the fundamental needs of the students in a research. This in fact can help to achieve desired faculty’s objective of Graduating on Time (GOT) where indirectly reflects the university achievement. On top o f that, students should be able to examine his/her research report for consistency throughout the document and be critical of the content, presentation and form at. With the introduction o f this BB Vol.3, the research degree supervisors may assist and advise the students in the design, timeline, development and completion of a research degree within the stipulated time. It gives both students and their respective supervisors an easy grasp o f the various processes designed in this code. Moreover, all of these have to be supported by good time management and writing habits to keep the momentum going. Hence, this handbook will also serve as a useful tool in preparing the students to ensure their research projects and presentation are deemed successful and aligned with the faculty's requirements.